Biomass production and psyllid resistance of Leucaena species grown as hedgerows on an upland Alfisol at Debre Zeit in the Ethiopian highlands - Berhe, Kahsay; Tothill, J.C.; Hanson, Jean (1998)
The genus Leucaena is one of the most important sources of multipurpose trees and shrubs for use in farming systems in the African tropics and subtropics. In previous studies, Kashsay and Tothill (1995) identified the superior performance of Leucaena pallida and L. diversifolia as highly productive sources of protein-rich fodder for use in the typical crop-livestock small-holder farms of the highland tropics of Ethiopia. These highlands are extensive in eastern and central Africa and are generally the more closely settled regions of the continent. Hence the application of this research is potentially wide. Such lands are also under increasing pressure from rapidly growing populations and the consequent encroachment on grazing lands by crop production (Mohamed Saleem and Abate Tedla 1995). Because of the close linkage between crops and livestock in draft power, nutrient cycling, and complementary productivity, it is important to sustain feed resources so that this all-important linkage can be maintained. The appearance on the world scene of the psyllid Heteropsylla cubana as a serious pest of L. leucocephala has been well documented by Moog (1992). Shelton and Brewbaker (1994), and Shelton and Jones (1995). The psyllid appeared only recently as a pest in Africa (Reynolds and Bimbuzi 1992). In Ethiopia, it was first observed in the Rift Valley area at Zwai in November 1993 and later at Debre Zeit in April 1994 (Mark Van de Wouw, personal communication). The insect is believed to have followed the rift valley line from the Mombasa Coast, where it was first observed in East Africa. To reach Zwai, the ILRI forage seed multiplication site, within the rift valley in Ethiopia, it traversed 1450 km (direct air distance) in only 15 months. Psyllid damaged leads to stunted growth and sometimes to the death of plants, reducing feed supply and feed quality for livestock (Moog 1992). Various studies in Hawaii (Austin et al. 1995), Florida (Austin et al 1996), and Australia (Castillo and Shelton (1994) have identified psyllid resistance in L. pallida, L. diversifolia, L. collinsii, and L. esculenta. This study was conducted at the ILRI Debre Zeit Research Site. Thirteen accessions of different Leucaena species and their hybrids, plus L. leucocephala cPeru (ILCA71) as a control were in the trial. Herbage dry matter production was measured. Plants were divided into groups 1, 2, and 3 and were harvested three, two and one time respectively. Psyllid damage was monitored weekly for seven weeks. Mature leaf samples from a number of plants of each accession were taken and freeze-dried fro analyses of parameters of nutritive value. The results of these studies are presented and discussed under three topics, viz, plant morphology biomass production, psyllid resistance and nutritive value.